Gender Roles in Reproductive, Productive and Community Spheres: A Comparative Study of Khudi, Pokhara - Dahal, Anita; Gurung , Manju; Subedi , Prem (Journal of Development and Social Engineering, 2025)
Gender roles are important in shaping social and economic life, particularly in developing societies. To explore the importance of gender role, this study examines the association between gender and participation in reproductive, productive, and community roles in Khudi, Pokhara Metropolitan City, Nepal. Based in Social Role Theory, this study aims to provide a general understanding of how gendered labor divisions are constructed and sustained across interconnected scopes of daily life. For this, a quantitative research method was employed, with data collected from 161 married and co-residing households using a semi-structured questionnaire. Descriptive statistics and Chi-square tests were applied to analyze gender-based differences in role allocation. The findings revealed that women were responsible for reproductive labor, including childcare, elder care, and household chores, while men maintain greater control over financial management and formal community roles. Women’s involvement in agricultural work and informal community development activities was significant, yet decision-making authority continues to support men. Although some tasks are increasingly shared, the imbalance between labor contribution and control persists. Demographic factors such as education and marital status showed limited influence on overall household engagement, underscoring the strength of structural and cultural norms. In sum, gender inequality in Khudi was maintained through interconnected reproductive, productive, and community roles. Policy interventions are needed to adopt integrated, gender transformative approaches that promote shared responsibility, recognize unpaid care work, and strengthen women’s decision-making power to foster equitable and sustainable social development.